2022
DOI: 10.1175/jhm-d-21-0073.1
|View full text |Cite
|
Sign up to set email alerts
|

The Orinoco Low-Level Jet and Its Association with the Hydroclimatology of Northern South America

Abstract: We investigated the relationship between the frequency of occurrence of the Orinoco Low-Level Jet (OLLJ) and hydroclimatic variables over northern South America. We use data from the ERA5 atmospheric reanalysis to characterize the spatial and temporal variability of the OLLJ in light of the LLJ-classification criteria available in the literature. An index for the frequency of occurrence of an LLJ was used, based on the hourly maxima of wind speed. The linkages among the OLLJ, water vapor flux, and precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Moreover, we calculated standardized anomalies of zonal wind speed at 925 hPa averaged over the OLLJ index area (6°–8°N and 67°–69°W), which was selected according to the recent work by Builes‐Jaramillo et al . (2022). Finally, we calculated Pearson correlations between the centre of the NASH minus NET SLP gradient anomaly and the OLLJ wind speeds anomalies for each of the DJF months.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we calculated standardized anomalies of zonal wind speed at 925 hPa averaged over the OLLJ index area (6°–8°N and 67°–69°W), which was selected according to the recent work by Builes‐Jaramillo et al . (2022). Finally, we calculated Pearson correlations between the centre of the NASH minus NET SLP gradient anomaly and the OLLJ wind speeds anomalies for each of the DJF months.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Builes‐Jaramillo et al . (2022) and Algarra et al . (2019) showed that the OLLJ is one of the mechanisms involved in the moisture transport from the tropical North Atlantic (TNA) towards the Amazon River basin and southern South America during December–February (DJF).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Equatorial South America, although not monsoonal per se [13,15,53,54], is linked to the SAM through LLJs (e.g., cross-equatorial flow, Orinoco) and its seasonal convection variability [24,25,36,55]. In the first case, the V-Index region (5 • S-5 • N, 65 • -75 • W; black boxes in Figure 1) was identified according to Wang et al [24] and captured the interhemispheric migration of rainfall crossing the equator.…”
Section: Cross-equatorial Flow Over Western Amazon and Precipitation ...mentioning
confidence: 99%
“…Wang et al [24] showed that precipitation variability over South America involves significant meridional migration and reversal of low-level winds between the south and north of the equator. These wind corridors in the lower atmosphere are Low-level jets (LLJs) and transport water vapor that modulates weather and climate [20,25,26]. Hence, LLJs are vital structures in the water vapor transport in the atmosphere, feeding the precipitation systems [26].…”
Section: Introductionmentioning
confidence: 99%